Better together? The role of social capital in urban social vulnerability. (June 2022) - Fraser, Timothy; Naquin, Nicole
Abstract: This study examines why some communities are more vulnerable than others, focusing on the transformative effect of residents' social capital on changing levels of vulnerability over time. We examine the case of Japan, the third largest economy in the world. Japan faces dozens of earthquakes, floods, and typhoons each year, but some communities are more socially vulnerable in the face of disaster than others. Drawing on difference-in-differences models and matching experiments, we test the effect of bonding, bridging, and linking social capital on vulnerability. We find that controlling for cities' governance capacity, resource demand based on population, and damage from recent hazards, higher levels of bonding social capital in a community leads to lower levels of vulnerability. However, other types of social capital do not immediately lead to lower vulnerability, implying that greater government support is necessary in these cases.